2020
DOI: 10.1038/s41598-020-69676-7
|View full text |Cite
|
Sign up to set email alerts
|

ABCC8 mRNA expression is an independent prognostic factor for glioma and can predict chemosensitivity

Abstract: Glioma is the most common primary intracranial tumor and is associated with very low survival rates. The development of reliable biomarkers can help to elucidate the molecular mechanisms involved in glioma development. Here the expression of ABCC8 mRNA, clinical characteristics, and survival information based on 1893 glioma samples from four independent databases were analyzed. The expression patterns of ABCC8 mRNA were compared by a Chi square test. The overall survival rate of gliomas was evaluated according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Evaluation of the effects of genetic depletion of ABCC8 in mouse models of metastatic breast cancer on metastasis to the central nervous system is merited. ABCC8 has been identified as an independent prognostic factor in glioma, with patients whose tumors expressed high levels of ABCC8 mRNA possessing improved patient survival 8 , consistent with our findings in patients with breast cancer. ABCC8 mRNA primary tumor expression in glioma patients was predictive of sensitivity to temozolomide chemotherapy 8 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Evaluation of the effects of genetic depletion of ABCC8 in mouse models of metastatic breast cancer on metastasis to the central nervous system is merited. ABCC8 has been identified as an independent prognostic factor in glioma, with patients whose tumors expressed high levels of ABCC8 mRNA possessing improved patient survival 8 , consistent with our findings in patients with breast cancer. ABCC8 mRNA primary tumor expression in glioma patients was predictive of sensitivity to temozolomide chemotherapy 8 .…”
Section: Discussionsupporting
confidence: 90%
“…ABCC8 has been identified as an independent prognostic factor in glioma, with patients whose tumors expressed high levels of ABCC8 mRNA possessing improved patient survival 8 , consistent with our findings in patients with breast cancer. ABCC8 mRNA primary tumor expression in glioma patients was predictive of sensitivity to temozolomide chemotherapy 8 . Modulation of ABCC8 expression may be relevant to the processes by which breast cancer cells exit the breast, enter the vasculature and/or lymphatics, reside in the lymph nodes, evade immune clearance, breach the blood-brain barrier and colonize the brain.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Tachon et al reported that the transcription factor Mesenchyme Homeobox 2 (MEOX2), a prognostic biomarker of LGG, is closely correlated to the overall survival (Tachon et al, 2019 ). Jiang et al further demonstrated that low expression of ATP binding cassette subfamily C member 8 (ABCC8) is an independent predictor of favorable prognosis in glioma patients (Zhou et al, 2020 ). In this study, we found that CFI is significantly upregulated in glioma tissues and strongly correlated with the prognosis of glioma patients in TCGA and CGGA cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The gene polymorphisms of CYP24A1 and CYP17A1 have been closely correlated with the risk of liver, lung, stomach, and prostate cancers in a Chinese population [ 24 , 25 ]. Another study has shown that the expression of ABCC8 mRNA can be used as an independent prognostic index in patients with glioma and can predict the sensitivity of gliomas to temozolomide [ 26 ].…”
Section: Discussionmentioning
confidence: 99%